μ-Opioid Receptor-Mediated AT1R-TLR4 Crosstalk Promotes Microglial Activation to Modulate Blood Pressure Control in the Central Nervous System - Gwo-Ching Sun; Jockey Tse; Yung-Ho Hsu; Chiu-Yi Ho; Ching-Jiunn Tseng; Pei-Wen Cheng (MDPI AG, 2021)
Opioids, a kind of peptide hormone involved in the development of hypertension, cause systemic and cerebral inflammation, and affects regions of the brain that are important for blood pressure (BP) control. A cause-and-effect relationship exists between hypertension and inflammation; however, the role of blood pressure in cerebral inflammation is not clear. Evidence showed that AT1R and μOR heterodimers' formation in the NTS might lead to the progression of hypertension. In this study, we investigated the formation of the μOR/AT1R heterodimer, determined its correlation with μORs level in the NTS, and explored the role of TLR4-dependent inflammation in the development of hypertension. Results showed that Ang II increased superoxide and Iba-1 (microgliosis marker: ionized calcium-binding adaptor molecule (1) levels in the NTS of spontaneously hypertensive rats (SHRs). The AT1R II inhibitor, losartan, significantly decreased BP and abolished superoxide, Iba-1, TLR4 expression induced by Ang II. Furthermore, losartan significantly increased nNsOSS1416 phosphorylation. Administration of a μOR agonist or antagonist in the NTS of WKY and SHRs increased endogenous μ-opioids, triggered the formation of μOR/AT1R heterodimers and the TLR4-dependent inflammatory pathway, and attenuated the effect of depressor nitric oxide (NO). These results imply an important link between neurotoxicity and superoxides wherein abnormal increases in NTS endogenous μ-opioids promote the interaction between Ang II and μOR, the binding of Ang II to AT1R, and the activation of microglia. In addition, the interaction between Ang II and μOR enhanced the formation of the AT1R and μOR heterodimers, and inactivated nNOS-derived NO, leading to the development of progressive hypertension.